STRATEGI MANAJEMEN PERUBAHAN DI SMK: MENJEMBATANI PENDIDIKAN VOKASI DAN KEBUTUHAN INDUSTRI 4.0 - Panji Arga, Bima; Moh. Al Ihsan; Joko; Basuki, Ismet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Rapid changes in the Industry 4.0 era demand strategic transformation in vocational high schools (SMK) to ensure graduates are workforce-ready. This article discusses change management strategies in SMKs, grounded in Lewin’s three-stage model (Unfreeze–Change–Refreeze) and Kotter’s eight-step model. The literature review covers curriculum adjustment to Industry 4.0 competencies, digital learning infrastructure, strengthening student soft skills, and active school–industry collaboration (Link and Match program). Key findings indicate that curriculum updates and technology integration enhance the alignment of vocational education with industry needs. Project-based learning, internships, and real-industry involvement effectively build students’ soft skills. Implementing Lewin and Kotter’s models provides a systematic framework that engages all stakeholders (teachers, students, industry, government) in the change process. Practical implications: Schools should form guiding coalitions, develop a shared vision, and allocate resources for teacher training and ICT facilities. Continuous collaboration between SMKs and industry significantly improves graduates’ job readiness.